Ambroxol Hydrochloride Improves Motor Functions and Extends Survival in a Mouse Model of Familial Amyotrophic Lateral Sclerosis - Bouscary, Alexandra; Quessada, Cyril; Mosbach, Althéa; Callizot, Noëlle; Spedding, Michael; Loeffler, Jean-Philippe; Henriques, Alexandre (Frontiers in Pharmacology, 2019)
Amyotrophic lateral sclerosis (ALS) is a multifactorial and fatal neurodegenerative disease. Growing evidences connects sphingolipid metabolism to the pathophysiology of ALS. In particular, levels of ceramides, glucosylceramides and gangliosides are dysregulated in the central nervous system and at the neuromuscular junctions of both animal models and patients. Glucosylceramide is the main precursor of complex glycosphingolipids that is degraded by lysosomal (GBA1) or non-lysosomal (GBA2) glucocerebrosidase. Here, we report that GBA2, but not GBA1, activity is markedly increased in the spinal cord, of SOD1G86R mice, an animal model of familial ALS, even before disease onset. We therefore investigated the effects of ambroxol hydrochloride, a known GBA2 inhibitor, in SOD1G86R mice. A presymptomatic administration of ambroxol hydrochloride, in the drinking water, delayed disease onset, protecting neuromuscular junctions and the number of functional spinal motor neurons. When administered at disease onset, ambroxol hydrochloride delayed motor function decline, protected neuromuscular junctions, and extended overall survival of the SOD1G86R mice. In addition, ambroxol hydrochloride improved motor recovery and muscle re-innervation after transient sciatic nerve injury in non-transgenic mice and promoted axonal elongation in an in vitro model of motor unit. Our study suggests that ambroxol hydrochloride promotes and protects motor units and improves axonal plasticity, and that this generic compound is a promising drug candidate for ALS.